Will ecosystem management supply woodland caribou habitat in northwestern Ontario? - Euler, David L. (Rangifer, 1998)
Ecosystem management is emerging as an important concept in managing forests. Although the basic conceptual idea is not new, important defining principles are developing that elucidate some of the specific attributes of ecosystem management. These principles include: the maintenance of all ecosystems in the managed forest, rhe emulation of natural disturbance patterns on rhe landscape and the insurance that structure and function of forested ecosystems are conserved. Forest management has an impact on woodland caribou (Rangifer tarandus caribou), although the presence of wolves (Canis lupus) and moose (Alces alces) in the same northern ecosystems also affects the caribou-forestry interacrion. Specific management for caribou as a featured species has been proposed, based on managing large landscape blocks. Ecosystem management would also produce habitat in a manner that might accomplish the goal of conserving woodland caribou as well as maintaining other important ecosystem functions.